Determinants And Efficiency Level Of Capital Goods Imports In Indonesia : Exploring Using Gravity Models - Sakti Prabowo (PT Wim Solusi Prima, 2021)
The study aims to investigate the significant factors and efficiency of capital goods imports in Indonesia. This study applies the stochastic frontier gravity approach (SFGA) to explore Indonesia's capital goods import values. The results suggest that there are positive impacts of some factors on the capital goods imports, including the GDP and population of the trading partners, distance, and regional cooperation such as the Free Trade Agreement (FTA). However, some factors, including the exchange rate and some global crises have significant negative impacts on the capital goods imports. The positive effects of FTA on capital goods imports may contribute to a reduction in the behind-the-border constraints. Furthermore, the trade efficiency resulting from the model may suggest that there is still a gap between potential and actual trade affected by the country-specific constraints, implying the requirement to investigate the appropriate reforms in Indonesia to reduce such constraints. Penelitian ini bertujuan untuk mengetahui faktor signifikan dan tingkat efisiensi impor barang modal di Indonesia. Penelitian ini menggunakan pendekatan stochastic frontier gravity (SFGA) untuk mengeksplorasi nilai impor barang modal Indonesia. Hasil penelitian menunjukkan terdapat dampak positif dari beberapa faktor terhadap impor barang modal, antara lain PDB dan populasi mitra dagang, jarak, dan kerjasama regional seperti Free Trade Agreement (FTA). Namun, beberapa faktor, seperti nilai tukar dan beberapa krisis global berdampak negatif signifikan terhadap impor barang modal. Efek positif FTA pada impor barang modal dapat berkontribusi pada pengurangan hambatan di belakang perbatasan. Selain itu, efisiensi perdagangan yang dihasilkan dari model tersebut dapat menunjukkan bahwa masih ada kesenjangan antara perdagangan potensial dan aktual yang dipengaruhi oleh kendala khusus negara, yang menyiratkan kebutuhan untuk menyelidiki reformasi yang tepat di Indonesia untuk mengurangi kendala tersebut.